Fatal respiratory disease due to a homozygous intronic ABCA3 mutation: A case report (2016)
Pulmonary surfactant is a complex mixture of lipids and proteins. Mutations in surfactant protein-C, surfactant protein-D, and adenosine triphosphate-binding cassette subfamily A member 3 have been related to surfactant dysfunction and neonatal respiratory failure in full-term babies. Adenosine triphosphate-binding cassette subfamily A member 3 facilitates the transfer of lipids to lamellar bodies. We report the case of patient with a homozygous intronic ABCA3 mutation. Case presentation: We describe a newborn full-term Colombian baby boy who was the son of non-consanguineous parents of mixed race ancestry (Mestizo), who was delivered with severe respiratory depression. Invasive treatment was unsuccessful and diagnosis was uncertain